Treatment-related fluctuations in guillain barre syndrome and the conundrum of additional cycles of plasmapheresis - Subasree Ramakrishnan; Veerendrakumar Mustare; Mariamma Philip; K Thennarasu; Sunder Periyavan (Annals of Indian Academy of Neurology, 2017)
Introduction: In Guillain Barre syndrome (GBS), worsening of weakness or disability after initial period of recovery or stabilization is described as treatment-related fluctuations (TRF). Aim: This study aims to describe the clinical characteristics and outcome of six patients with GBS and TRF. Patients and Methods: Six patients with GBS fulfilling NINCDS criteria, evaluated at a tertiary care university hospital during 2008–2017, were diagnosed to have TRF. They form the basis of this report. Results: All patients were men and their mean age was 40 years. At presentation, mean duration of illness was 15 days; the illness had plateaued in three and progressive in other three patients. Two of the four patients had variant GBS. Initially, five patients were treated with large volume plasmapheresis (LVPP) and one patient with methyl prednisolone. At 17–28 days after disease onset, three patients developed new neurologic deficits (bilateral facial paresis in two; paralytic ileus in one). Other three patients with worsening of limb weakness (medical research council sum score of >5) and disability (Hughes disability grade by ≥1) fulfilled Kleyweg's criteria for TRF. All the six patients were treated with the completion of five cycles or additional cycles of LVPP. Conclusion: Awareness about TRF is essential for correct diagnosis and management of patients with GBS.